Psychological and Social Determinants of HIV: Path Analysis Evidence from Jepara, Central Java - Ita Fijanah Puspita; Uki Retno Budihastuti; Vitri Widyaningsih (Journal of Health Promotion and Behavior, 2019)
Background: HIV/AIDS was a global problem as a challenge in health discipline and a very important burden of disease to be addressed. Moreover, it had high mortality. This study aimed to analyze the risk factors for HIV/AIDS infection.Subjects and Method: This was a case control study conducted in Jepara, Central Java, from April to May 2019. A sample of 200 study subjects was selected by fixed disease sampling. The dependent variable was HIV/AIDS. The independent variables were age, gender, unsafe sex behavior, sexual orientation, frequency of intercourse, injection drug abuse, social capital, perceived susceptibility, perceived seriousness, perceived threat, self-efficacy, and geographical location. The data were obtained from medical record and questionnaire. The data were analyzed by path analysis.Results: HIV / AIDS had a direct relationship with the frequency of sexual intercourse (b= 1.23; 95% CI= 0.27 to 2.19; p= 0.012), injecting drug use (b = 2.19; 95% CI= 0.01 to 4.37; p= 0.049), behavior unsafe sex (b= 3.10; 95% CI= 2.21 to 3.99; p <0.001), and sexual orientation (b= 3.69; 95% CI= 1.35 to 6.04; p= 0.002). HIV / AIDS had an indirect relationship with perceptions of threats, gender, geographical location, social capital, perceptions of vulnerability, perception of seriousness, self-efficacy, and age.Conclusions: HIV / AIDS has a direct relationship with the frequency of sexual relations, sexual orientation, unsafe sexual behavior, and injecting drug use. HIV / AIDS has an indirect relationship with age, gender, perception of vulnerability, perception of seriousness, perception of threats, self-efficacy, social capital, and geographical location.Keywords: HIV / AIDS, sexual behavior, social capital, path analysisCorrespondence: Ita Fijanah Puspita, Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: itapuspita713@gmail.com. Mobile: 081347970482.Journal of Health Promotion and Behavior (2019), 4(1): 43-54https://doi.org/10.26911/thejhpb.2019.04.01.05